Study on the Metabolic Transformation Rule of Enrofloxacin Combined with Tilmicosin in Laying Hens - Jingchao Guo; Liyun Zhang; Yongxia Zhao; Awais Ihsan; Xu Wang; Yanfei Tao (Metabolites, 2023)
There is often abuse of drugs in livestock and poultry production, and the improper use of drugs leads to the existence of a low level of residues in eggs, which is a potential threat to human safety. Enrofloxacin (EF) and tilmicosin (TIM) are regularly combined for the prevention and treatment of poultry diseases. The current studies on EF or TIM mainly focus on a single drug, and the effects of the combined application of these two antibiotics on EF metabolism in laying hens are rarely reported. In this study, liquid chromatography-tandem mass spectrometry (LC-MS/MS) was used to determine the residual EF and TIM in laying hens and to investigate the effect of TIM on the EF metabolism in laying hens. In this paper, we first establish a method that can detect EF and TIM simultaneously. Secondly, the results showed that the highest concentration of EF in the egg samples was 974.92 ± 441.71 μg/kg on the 5th day of treatment. The highest concentration of EF in the egg samples of the combined administration group was 1256.41 ± 226.10 μg/kg on the 5th day of administration. The results showed that when EF and TIM were used in combination, the residue of EF in the eggs was increased, the elimination rate of EF was decreased, and the half-life of EF was increased. Therefore, the use of EF and TIM in combination should be treated with greater care and supervision should be strengthened to avoid risks to human health.